PENGARUH PENERAPAN PROBLEM BASED LEARNING TERHADAP KEPERCAYAAN DIRI DAN HASIL BELAJAR MATEMATIKA SISWA DI KELAS VII SMP NEGERI 1 BATANG ONANG KABUPATEN PADANG LAWAS UTARA - Siregar, Sri Handayani (JURNAL MathEdu (Mathematic Education Journal), 2024)
Study This is study quantitative form design quasi experiment Which used class control And class experiment. Class experiment apply Problem Based Learning in process learning with material Rectangle And Rectangle Long. Population in study This is all over student class VII SMP Negeri 1 Batang Onang Kabupaten Padang Lawas Utara. And sample in study This 32 student For every class use Clusters Random Sampling . Use Model learning cooperative type Problem Based Learning (PBL) give influence significant to trust self And results Study student mathematics. The level of student confidence after using problem based learning from 32.94 become 84.16 And results Study mathematics student as big as 63.75 And after application model learning mark average become 87.34. Got it influence Which significant between application Problem Based Learning to trust self And results Study mathematics student in class VII SMP Negeri 1 Batang Onang Kabupaten Padang Lawas Utara. Class with apply model learning type Problem Based Learning to trust self And results Study student give influence significance. This showed results questionnaire with mark sig < 0.05 that is 0.01 < 0.05 And t count > t table ie 3,343 > 2.04. As well as mark results test with mark sig < 0.05 that is 0.00 < 0.05 And t count > t table ie 4,077 > 2.04, It means there is influence Which significant between application Problem Based Learning (PBL) to trust self student and result Study student. Keywords : Results Learning, Trust Self, PBL.